Evidence for the rare decay [sigma]+→p[mu]+[mu]- - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Dordei, Francesca; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; et al. (Physical review letters, 2018)
A search for the rare decay Σ+→pμ+μ− is performed using pp collision data recorded by the LHCb experiment at center-of-mass energies √s=7 and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. An excess of events is observed with respect to the background expectation, with a signal significance of 4.1 standard deviations. No significant structure is observed in the dimuon invariant mass distribution, in contrast with a previous result from the HyperCP experiment. The measured Σ+→pμ+μ− branching fraction is (2.2+1.8−1.3)×10−8, where statistical and systematic uncertainties are included, which is consistent with the standard model prediction.